Effect of Hydrogen Peroxide on the Recovery of Valuable Metals from Spent LiNi0.6Co0.2Mn0.2O2 Batteries. Issue 4 (23rd February 2022) - Cheng, Xiangyu; Guo, Guanghui; Cheng, Yukun; Liu, Mingxiu; Ji, Jiaxing
Abstract : Considering the increasing price of raw materials and environmental pollution, the recycling of used lithium battery cathode materials has very important economic and environmental value. In this experiment, a green recycling method is used to recover valuable metals from spent LiNi0.6 Co0.2 Mn0.2 O2 batteries using DL‐malic acid and H2 O2 as a leaching system. The effects of reaction temperature, acid concentration, H2 O2 volume concentration, reaction time, and solid–liquid ratio on the leaching efficiency are investigated by orthogonal and single variable condition experiments. Under the optimum conditions, the leaching efficiencies of Ni, Co, Mn, and Li are 96.2%, 97.1%, 97.6%, and 98.1%, respectively, while the leaching efficiency of Al is only 3.5%. The effect of H2 O2 on the leaching process is further investigated by macroscopic characterization and kinetic analysis. The study indicates that the leaching process is controlled by a chemical reaction in the absence of H2 O2, and the leaching process after the addition of H2 O2 is controlled by the chemical reaction process and the diﬀusion process. Abstract : Herein, DL‐malic acid and H2 O2 are used as the leaching system to conduct eﬃcient green leaching of spent LiNi0.6 Co0.2 Mn0.2 O2 batteries. The kinetic analysis indicates that the leaching process is controlled by chemical reaction in the absence of H2 O2, and the leaching process after the addition of H2 O2 is controlled by the chemical reaction process and the diﬀusion process.